Aminoglycoside Allergic Reactions - Lindsey M. Childs-Kean; Kristy M. Shaeer; Sheeba Varghese Gupta; Jonathan C. Cho (MDPI AG, 2019)
Aminoglycosides are antimicrobial agents that are primarily used for infections caused by Gram-negative pathogens. The purpose of this article is to review the allergic reactions reported in the published literature to aminoglycoside antibiotics. A thorough PubMed search was conducted and excluded non-allergic adverse reactions to aminoglycosides. Allergic reactions to aminoglycosides occur infrequently, but can include cutaneous reactions as well as systemic reactions, including anaphylaxis. Of the evaluated aminoglycosides, gentamicin had the most reported allergic reactions, including the most reports of anaphylaxis, followed by tobramycin, and then amikacin. Most reports of allergic reactions occurred in patients who had a prior exposure to some dosage form of an aminoglycoside. Cross-reactivity among aminoglycosides is common and occurs due to the similarities in their chemical structures. Desensitization protocols to tobramycin have been described in the literature.